2011
DOI: 10.1016/j.virusres.2011.06.029
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the spike protein of human coronavirus NL63 in receptor binding and pseudotype virus entry

Abstract: The spike (S) protein of human coronavirus NL63 (HCoV-NL63) mediates both cell attachment by binding to its receptor hACE2 and membrane fusion during virus entry. We have previously identified the receptor-binding domain (RBD) and residues important for RBD-hACE2 association. Here, we further characterized the S protein by investigating the roles of the cytoplasmic tail and 19 residues located in the RBD in protein accumulation, receptor binding, and pseudotype virus entry. For these purposes, we first identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 70 publications
3
23
0
1
Order By: Relevance
“…Global and Kilifi spike sequences were aligned and compared to the HCoV-NL63 reference strain (NC_005831) to reveal the spike amino acid differences ( Figure 4A). These patterns further supported the conclusion that 2 major genotypes of HCoV-NL63 (A and B) circulated in Kilifi over the observation period ( The binding domain for the cellular receptor for HCoV-NL63 (ACE2) resides in the central portion of the spike protein, residues 476-616 [42,43], identified by the orange horizontal band marked RBD in Figure 4A top panel. Differences in this region were marked in Figure 4A with several amino acid polymorphisms persisting in multiple samples (eg, I507L, E471D, E572A), suggesting genetic drift or possible positive advantage for these residues.…”
Section: Resultssupporting
confidence: 74%
“…Global and Kilifi spike sequences were aligned and compared to the HCoV-NL63 reference strain (NC_005831) to reveal the spike amino acid differences ( Figure 4A). These patterns further supported the conclusion that 2 major genotypes of HCoV-NL63 (A and B) circulated in Kilifi over the observation period ( The binding domain for the cellular receptor for HCoV-NL63 (ACE2) resides in the central portion of the spike protein, residues 476-616 [42,43], identified by the orange horizontal band marked RBD in Figure 4A top panel. Differences in this region were marked in Figure 4A with several amino acid polymorphisms persisting in multiple samples (eg, I507L, E471D, E572A), suggesting genetic drift or possible positive advantage for these residues.…”
Section: Resultssupporting
confidence: 74%
“…N-terminally FLAG-tagged human IFITM1, IFITM2, and IFITM3 and their mutants were also cloned into the pQCXIP vector (Clontech) between the NotI and BamHI sites (29). Plasmids expressing HCoV-OC43 S and HE proteins, VSV G protein, H1N1 IAV (A/WSN/33) HA and neuraminidase (NA), Ebola virus (EBOV) GP protein, LASV GP protein, murine leukemia virus (MLV) envelope protein, and HCoV-NL63 and SARS-CoV spike proteins were described previously (62,63). The MERS-CoV spike gene (GenBank accession number AFS88936) was synthesized by GeneScript, cloned into the pCAGGS vector, and confirmed by DNA sequence analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that, at least in SARS-CoV, a receptor-binding domain on the S protein mediates the attachment of said virus to its cellular receptor, angiotensin-converting enzyme 2 (ACE2) [33,34]. Lin et al found that HCoV-NL63 also makes use of the S protein-ACE2 mechanism for cell entry [35].…”
Section: Coronavirusesmentioning
confidence: 99%